Analisis Kestabilan Transien pada Project Pelabuhan Kontainer Pakistan : Transient Stability Analysis in Pakistan Deep Water Container Port - Isa Hafidz (UPPM Akademi Komunitas Semen Indonesia, 2019)
Power system will operate in a stable condition if there is a balance between the power of mechanical prime mover and electric power output. Each increment or decrease the load must be followed with changes mechanical prime mover generator power. If it does not immediately adjust then would make the system become unstable or loss of synchronization. Project of Pakistan Deep Water Container Port, which provided the plant duty these days, transient stability must to be studied to determine system realibility during tansient disturbance. This final project is focused on transient stability include frequency response, the angle of the rotor, and voltage. Load shedding mechanism is performed by considering short circuit, motor starting, and the generator shedding phenomenon. Some of our results are not intuitive